2019
DOI: 10.22267/rcia.193601.94
|View full text |Cite
|
Sign up to set email alerts
|

Fumigant toxicity of eugenol and its negative effects on biological development of Callosobruchus maculatus L

Abstract: The protection of stored products from insect damages, when accomplished, is mostly relying on the application of synthetic insecticides with serious health and environmental issues in addition to risks of selection of resistant insect populations associated with such practice. The use of plants derived compounds have been presented as sound strategy for sustainable insect pest management. Eugenol is an aromatic component of natural occurrence in essential oils of numerous plants. known for its repellent and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
(45 reference statements)
1
3
0
Order By: Relevance
“…Coleoptera: Chrysomelidae) in the fumigant test, with LC 50 value close to the one we obtained in the lter paper tests(González et al 2019). Also, the results ofMartínez et al (2018) measurement of the lethal time gave similar results of 50% lethality, as our LT 50 values, although the nal mortality (i.e., close to 100%) was obtained faster than in our experiment.…”
supporting
confidence: 88%
“…Coleoptera: Chrysomelidae) in the fumigant test, with LC 50 value close to the one we obtained in the lter paper tests(González et al 2019). Also, the results ofMartínez et al (2018) measurement of the lethal time gave similar results of 50% lethality, as our LT 50 values, although the nal mortality (i.e., close to 100%) was obtained faster than in our experiment.…”
supporting
confidence: 88%
“…Previous studies have shown that the insecticidal efficacy of peppermint oil Heydari et al, (2020). Eugenol has been proven effective in controlling a wide range of pests such as Aedes aegypti (Adhikari et al, 2022), Musca domestica (Silva et al, 2020), Callosobruchus maculatus (González et al, 2019). Two nano forms have highly significant effect than the traditional forms.…”
Section: Discussionmentioning
confidence: 99%
“…However, as already addressed in the present investigation, neglecting the unintended effects of biorational insecticides can represent a serious flaw for these insect management tools. Indeed, insects exposed to sublethal doses of biorational insecticides can change their physiology or behavior in a way that can increase or compromise the efficacy of these management tools. This implication should be seriously considered.…”
Section: Unintended Outcomesmentioning
confidence: 99%